Direct Quantitative Gas Chromatographic Separation of C(2)-C(6) Fatty Acids, Methanol, and Ethyl Alcohol in Aqueous Microbial Fermentation Media - Rogosa, M. (1968)
A method is described for the direct quantitative gas chromatographic separation of C(2)-C(6) lower fatty acid homologues, methanol, and ethyl alcohol in aqueous microbial fermentation media. A hydrogen flame detector and a single-phase solid column packing, comprising beads of a polyaromatic resin (polystyrene cross-linked with divinyl benzene), were employed. Direct injections of 1 to 10 μliters of aqueous culture supernatant fluids were made. Quantitative recoveries of C(2)-C(6) acids added to culture supernatant fluids were obtained.